Quartz Enhanced Photoacoustic Spectroscopy Based on a Custom Quartz Tuning Fork - Maxime Duquesnoy; Guillaume Aoust; Jean-Michel Melkonian; Raphaël Lévy; Myriam Raybaut; Antoine Godard (Sensors, 2019)
We have designed and fabricated a custom quartz tuning fork (QTF) with a reduced fundamental frequency; a larger gap between the prongs; and the best quality factor in air at atmospheric conditions ever reported, to our knowledge. Acoustic microresonators have been added to the QTF in order to enhance the sensor sensitivity. We demonstrate a normalized noise equivalent absorption (NNEA) of 3.7 × 10−9 W.cm−1.Hz−1/2 for CO2 detection at atmospheric pressure. The influence of the inner diameter and length of the microresonators has been studied, as well as the penetration depth between the QTF’s prongs. We investigated the acoustic isolation of our system and measured the Allan deviation of the sensor.